Dinamika Pengelolaan Lahan Masyarakat Di Desa Berbura Pasca Penetapan Taman Nasional Gunung Maras - Karina; Delvia Jusmi; Stephen Paul T.M; Muhammad Syaiful Anwar (CV. Multi Kreasi Media, 2022)
Abstract- National Parks are one form of effort in order to preserve the environment along with the flora and fauna that exist in the area. This is to protect these ecosystems from extinction and protect the forest. Likewise, Mount Maras National Park is designated to protect and preserve the ecosystems in it. However, various problems arise related to the Management of Community Land around the Mount Maras National Park area, especially the people in Berbura Village. There was a dynamic in the management of the community's land after the establishment of the Mount Maras National Park where the community was bound by rules that made them not free to manage the land that had been inherited by their ancestors. In this study, researchers want to know how the Berbura village community faces the dynamics that occur in managing land and how the rights and authorities of the village in terms of land management are. Through descriptive qualitative research methods, researchers found the fact that the people in Berbura Village can still manage their land but are not free and have a lack of knowledge about the National Park. They continue to use farming or gardening as a livelihood.